问题 解答题
(1)(-1)3•(3a3b2)3•(-
2
3
a2b3)3

(2)[-2(x-y)2]2•(y-x)3
(3)(-ab)3(a2+ab+1)+(-ab22(-2a2
(4)2(x-2)(x+4)
(5)(3x+4y)(2x-3y)
(6)(x-1)(x+1)(x2+1)
(7)8(
1
2
x-
3
2
)(2x+6)

(8)(-2a+3b)2-(3a+2b)2
(9)9962-995×997.
答案

(1)原式=-27a9b6•(-

8
27
a6b9)=8a15b15

(2)原式=4(x-y)4•(y-x)3=4(y-x)7

(3)原式=-a5b3-a4b4-a3b3-2a4b4=-a5b3-3a4b4-a3b3

(4)原式=2x2+4x-16;

(5)原式=6x2-xy-12y2

(6)原式=(x2-1)(x2+1)=x4-1;

(7)原式=8x2-72;

(8)原式=(-2a+3b+3a+2b)(-2a+3b-3a-2b)=(a+5b)(-5a+b)=-5a2+5b2-24ab;

(9)原式=9962-(996-1)×(996+1)=9962-(9962-1)=1.

单项选择题 A1型题
单项选择题